Implantation of deuterium and helium ions into composite structure with tantalum coating - Bobkov, V.V.; Tishchenko, L.P.; Kovtunenko, Yu.I.; Tsapenko, O.B.; Skrypnik, A.O.; Logachev, Yu.E.; Gamayunova, L.A. (Вопросы атомной науки и техники, 2018)
Processes of retention and thermal release of implanted deuterium and helium from tantalum coatings of multilayer composite structure by thermodesorption spectrometry were investigated. The dependences of amount of accumulated deuterium and helium, and the shape of thermal desorption spectra as functions of the D⁺ and He⁺ ions fluencies and of the temperature of irradiation were shown. Possible mechanisms of these processes are proposed.